2016
DOI: 10.1186/s12284-016-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Rice Chloroplast Genome Variation Architecture and Phylogenetic Dissection in Diverse Oryza Species Assessed by Whole-Genome Resequencing

Abstract: BackgroundChloroplast genome variations have been detected, despite its overall conserved structure, which has been valuable for plant population genetics and evolutionary studies. Here, we described chloroplast variation architecture of 383 rice accessions from diverse regions and different ecotypes, in order to mine the rice chloroplast genome variation architecture and phylogenetic.ResultsA total of 3677 variations across the chloroplast genome were identified with an average density of 27.33 per kb, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 80 publications
(95 reference statements)
1
44
0
Order By: Relevance
“…SSRs were widely dispersed in chloroplast genomes, and have been extensively used in population genetics and molecular phylogenetic researches [40,41]. In this study, 1205 SSRs were identified in five Alpinia chloroplast genomes, including two accessions of A. oxyphylla, A. katsumadai, A. zerumbet, and A. pumila ( Figure 3 and Table S6).…”
Section: Ssrs and Long Repeats Analysesmentioning
confidence: 89%
“…SSRs were widely dispersed in chloroplast genomes, and have been extensively used in population genetics and molecular phylogenetic researches [40,41]. In this study, 1205 SSRs were identified in five Alpinia chloroplast genomes, including two accessions of A. oxyphylla, A. katsumadai, A. zerumbet, and A. pumila ( Figure 3 and Table S6).…”
Section: Ssrs and Long Repeats Analysesmentioning
confidence: 89%
“…SSRs are These markers are widely used in population genetics and breeding program studies 44, 45 because of their high polymorphism even within species, due to slipped-strand mispairing on a single DNA strand during DNA replication 46 . In this study, 1,043 SSRs were identified in sixteen Lilium cp genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of genomic SNPs provides an opportunity to apply these data to genome-based association studies in the future. Recent studies have utilized whole mitochondrial or plastid genome approaches to detect SNPs in plants, which showed that organellar SNP markers are a powerful genetic resource for germplasm differentiation, purification, and population genetics (Mcpherson et al, 2013;Sabir et al, 2014;Wei et al, 2016;Shen et al, 2017). The Pyropia species is characterized by a high proportion of organellar DNA and a small organellar genome size, which makes sequencing the organellar genomes affordable and convenient without the need 1 http://www.fao.org/fishery/factsheets/en for prior isolation or amplification (Wang et al, 2013;Kong et al, 2014;Xu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%